Toward Biomimetic Scaffolds for Tissue Engineering: 3D Printing Techniques in Regenerative Medicine - Chung, Justin J.; Im, Heejung; Kim, Soo Hyun; Park, Jong Woong; Jung, Youngmee (Frontiers in Bioengineering and Biotechnology, 2020)
3D printing technology allows fabricating complex and precise structures by stacking materials layer-by-layer. The fabrication method has a strong potential in regenerative medicine field to produce customizable and defect fillable scaffolds for tissue regeneration. Plus, biocompatible materials, bioactive molecules, and cells can be printed together or separately to enhance scaffolds, which can save patients who suffer from shortage of transplantable organs. There are various 3D printing techniques which depends on the types of materials, or inks, used. Here, different types of organs (bone, cartilage, heart valve, liver, and skin) that are aided by 3D printed scaffolds, and printing methods that are applied in the biomedical fields are reviewed.